Newly isolate highly potential xylanase producer strain from various environmental sources. (October 2018) - Lee, S.H.; Lim, V.; Lee, C.K.
Abstract: Xylanase is an enzyme that degrades hemicelluloses. The goal of the present study was to investigate the production of xylanase by fungi via the solid substrate fermentation (SSF) process using sugarcane bagasse and palm kernel cake as substrate. During preliminary screening, 15 potential xylanase producer strains were isolated from 9 different environmental sources. Eight out of the 15 isolates produced positive results in the submerged fermentation process and clear-zone formation analysis. The decayed wood isolate had the highest xylanase activity, at 154.2 U/g in the secondary screening process. This isolate, identified as Aspergillus niger, was selected for further study. The maximum xylanase activity of 456.4 U/g was obtained under optimized conditions of 6 g of substrate, 75% (w/w) moisture content, temperature of 34 °C, and initial medium of pH 6 supplemented with 2% (w/v) glucose and 0.25 mM manganese ions. This activity was 1.5-fold higher than that reported in previous studies. These results illustrate that an increased xylanase yield can be obtained via SSF using agro-industry residual products such as palm kernel cake and sugarcane bagasse as substrates, which would reduce the overall cost of producing xylanase. Highlights: 15 xylanase producer strains were isolated from 9 different environmental sources. Production of xylanase using sugarcane bagasse and palm kernel cake as substrate. Aspergillus niger DWA produced maximum xylanase activity of 456.4 U/g. High xylanase yield can be obtained via SSF which could reduce production cost.